UMP establishes collaboration with PKPP in the agriculture sector - Mimi Rabita, Abdul Wahit (2023)
KUALA LUMPUR, 26 May 2023 – Recently, Universiti Malaysia Pahang (UMP) has formed a collaboration with the Pahang State Agricultural Development Corporation (PKPP) to develop the fields of farming, agriculture, and livestock.